Penerapan Model Make A Match untuk Meningkatkan Pembelajaran Bahasa Arab pada Sdit Al-Qonita Palangka Raya - Hunainah Hunainah (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2016)
This study is motivated by the writer’s preliminary observation to some of the students at SDIT; the mastery of their Arabic vocabularies is not maximal yet. It could be caused by many factors; including the teachers who tend using the old methods such as a drill or with the help of images in teaching Arabic. The purpose of this study is to know the quality of learning Arabic class V SDIT Al-Qonita Palangka Raya by using make a matching model. The approach used in this study is a qualitative descriptive approach. The data collection is through observation, interviews, and documentation, then analyzed descriptively through the stages of data reduction, data presentation, and conclusions. The results showed that this model is very suitable to be used in learning Arabic, not only proved to be loved by the students in class V SDIT Al-Qonita Palangka Raya but also effective to achieve the related learning objectives. In the case of learning Arabic in SDIT Al-Qonita Palangka Raya, considering the class is not big class, so they make a matching model is able to improve the learning in general, in terms of making students understand easily, easy of evaluation, easy to master, easy to train these four language skills (istima', Kalam, qira'ah, and kitabah).